Fractional microablative CO2 laser for vulvovaginal atrophy in women treated with chemotherapy and/or hormonal therapy for breast cancer: a retrospective study. Issue 10 (October 2016) - Pagano, Tiziana; De Rosa, Pasquale; Vallone, Roberta; Schettini, Francesco; Arpino, Grazia; De Placido, Sabino; Nazzaro, Giovanni; Locci, Mariavittoria; De Placido, Giuseppe
Abstract: Objectives: Breast cancer is one of the most common malignancies in women. Hormonal treatment and chemotherapy induce a transient or permanent menopause status. Vulvovaginal atrophy (VVA) is a frequent debilitating symptom of menopause that is best treated with local or systemic estrogen formulations. Because estrogens drive the growth of the majority of breast cancers, most effective VVA therapies are precluded. The aim of this study was to evaluate the effects of fractional microablative CO2 laser on sexual function and in relieving symptoms in women with breast cancer and VVA induced or exacerbated by iatrogenic menopause. Methods: This retrospective study included 26 women affected by hormone-receptor positive breast tumors and treated for VVA symptoms with the fractional microablative CO2 laser system. Every 30 to 40 days, women underwent a cycle of treatment for a total of three cycles. During each cycle, women underwent a gynecological examination and completed visual analog scale questionnaires designed to assess (1) the degree of symptoms and (2) procedure-related discomfort. Results: Treatment resulted in a significant regression of VVA symptoms and procedure-related discomfort versus baseline ( P < 0.001 in almost all cases). No adverse reactions were observed nor reported by women. Conclusions: Fractional microablative CO2 laser treatment is associated with a significant improvement of VVA symptoms in women affected by hormone-driven breast cancer. This procedure has the advantage of relieving iatrogenic/physiological VVA symptoms without resorting to contraindicated estrogen preparations, which have been the most effective therapy thus far.